Character Formation, Religious Education, and School Environment Examining Their Impact on Digital Literacy-Driven Communication - Diani Austin; Nursyifa Karimah; Elsa Herliyana (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study investigates the impact of character formation, religious education, and school environment on digital literacy-driven communication. The research aims to understand how these factors shape individuals' abilities and behaviors in digital communication. Employing a qualitative research model, data collection will involve interviews and observations. The sampling technique will employ purposive sampling to ensure representation across various demographics. Data analysis will employ thematic analysis to identify patterns and themes within the collected data. The study anticipates revealing insights into how character formation, religious education, and school environment interact to influence digital literacy and communication practices, contributing to a deeper understanding of the dynamics between traditional values and digital engagement.